Preparation, characterization, and thermal properties of poly (methyl methacrylate)/boron nitride composites by bulk polymerization. Issue 9 (13th May 2014) - Qin, Lili; Li, Guohua; Hou, Jun; Yu, Xiaoyan; Ding, Huili; Zhang, Qingxin; Wang, Nongyue; Qu, Xiongwei
<x xml:space="preserve">Abstract</x> Poly (methyl methacrylate)/boron nitride (PMMA/BN) composites were prepared by dispersing BN particles into methyl methacrylate monomer phase by bulk polymerization method. BN particles modified with silane coupling agent, γ‐methacryloxypropyl trimethoxy silane, were characterized by Fourier transform infrared spectroscopy and thermogravimetric analysis. Effects of modified BN particle content on thermal conductivity were investigated, and the experimental values were compared with those of theoretical and empirical models. With 16 wt% of BN particles, the thermal conductivity of the composite was 0.53 W/(m·K), 1.8 times higher than that of pure PMMA. The microstructures of the PMMA/BN composites were examined by scanning electron microscopy, energy‐dispersive X‐ray analysis, and transmission electron microscopy. Dynamic mechanical analysis and thermogravimetric analysis traces also corroborated the confinement of the polymer in an inorganic layer by exhibiting an increase in glass‐transition temperatures and weight loss temperatures in the thermogram. Mechanical properties and electrical insulation property of the PMMA/BN composites were also determined. These results showed that PMMA/BN composites may offer new technology and business opportunities. POLYM. COMPOS., 36:1675–1684, 2015. © 2014 Society of Plastics Engineers